The effectiveness of occupational therapy handwriting intervention for children with motor coordination issues : a systematic review - Mahfuzah Zainol,; Masne Kadar,; Nor Afifi Razaob,; Farahiyah Wan Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Handwriting difficulty is one of the main issues among school children, especially for those with motor coordination issues. The aim of this systematic review is to evaluate the effectiveness of occupational therapy interventions in handwriting components for children with motor coordination issues. Current research articles were systematically searched according to the PRISMA guidelines. Two hundred and sixty-eight (n=268) research articles were identified; however, only ten (n=10) were eligible to be evaluated for this study. Studies were appraised by using McMaster Critical Review Form-Quantitative Studies. Descriptive synthesis was executed due to the heterogeneity of included studies. The review found various types of intervention conducted by occupational therapists to have a positive effect on handwriting performance components among children with motor coordination issues. Types of intervention used were visual, motor, perceptual, sensory, activity of daily living skills, training device and assistive technology and specific handwriting programs. Most handwriting intervention showed effectiveness to improve handwriting performance in motor function, visual and perceptual components. Future research should focus on homogeneity of Occupational Therapy (OT) intervention to improve handwriting performance by using specific handwriting programmes and similar standardised evaluation instruments. Practitioners of OT intervention should consider collaboration with teachers, parents and other health professionals to expedite effectiveness of intervention in handwriting performance components.